HOW KOMPAS.COM FRAMED INDONESIA GOVERNMENT’S POLICY ON COVID-19 - Ruben Elizer Sitepu; Ni Made Ras Amanda Gelgel; Ade Devia Pradipta; Aloysia Vira Herawati; Dwi Ajeng Widarini (ASPIKOM Jabodetabek Region, 2021)
The COVID-19 pandemic is one of the most widely covered news stories in 2020, particularly in March 2020, when the COVID-19 virus made its first appearance in Indonesia. The government also responded to the Covid-19 virus’s entry into Indonesia by issuing health, social, and economic policies. Reporting on the government’s actions is undoubtedly one of the Indonesian media’s objectives. Kompas.com is one of the media outlets that publish news about the government’s actions. The seven news articles published by Kompas.com in March 2020 are the subject of this study. This research employs a qualitative approach and analyzes data using Robert N. Entman’s framing model analysis. According to Robert Entman’s analysis, news framing can be viewed in two dimensions: issue selection and aspect highlighting. By analyzing seven news articles published by Kompas.com using Robert N. Entman’s framing model, it was concluded that the construction of Kompas.com news was that the government was having difficulty dealing with the spread of COVID-19 in Indonesia.